Answer:
700.39cm
Step-by-step explanation:
For a horizontal distance of 30cm, the drop is 1cm, now we need to get the drop for horizontal distance of 700 cm to maintain the same slope
Using the concept of cross multiplication
30cm=1 cm drop
700 cm=x
30x=700
X=700/30=70/3=23 ⅓
Utilizing pythagoras theorem, the length of pipe will be
L=√(23⅓)²+700²
L=700.38878092417 cm
Rounded off, the length is approximately 700.39 cm
The <em>missing</em> pattern behind the sequence 7, 11, 2, 18, -7 is described by the formula
, equivalent to the <em>recurrence</em> formula
.
<h3>What is the missing element in a sequence?</h3>
A sequence is a set of elements which observes at least a <em>defined</em> rule. In this question we see a sequence which follows this rule:
(1)
Now we prove that given expression contains the pattern:
n = 0
7
n = 1
7 + (- 1)² · 2² = 7 + 4 = 11
n = 2
7 + (- 1)² · 2² + (- 1)³ · 3² = 11 - 9 = 2
n = 3
7 + (- 1)² · 2² + (- 1)³ · 3² + (- 1)⁴ · 4² = 2 + 16 = 18
n = 4
7 + (- 1)² · 2² + (- 1)³ · 3² + (- 1)⁴ · 4² + (- 1)⁵ · 5² = 18 - 25 = - 7
The <em>missing</em> pattern behind the sequence 7, 11, 2, 18, -7 is described by the formula
, equivalent to the <em>recurrence</em> formula
.
To learn more on patterns: brainly.com/question/23136125
#SPJ1
This is a guess using logic, but my answer for this is that she concluded that she walked faster in the first 15 minutes. An increase in speed would increase the distance she walked in that amount of time
Answer:
![\displaystyle log_\frac{1}{2}(64)=-6](https://tex.z-dn.net/?f=%5Cdisplaystyle%20log_%5Cfrac%7B1%7D%7B2%7D%2864%29%3D-6)
Step-by-step explanation:
<u>Properties of Logarithms</u>
We'll recall below the basic properties of logarithms:
![log_b(1) = 0](https://tex.z-dn.net/?f=log_b%281%29%20%3D%200)
Logarithm of the base:
![log_b(b) = 1](https://tex.z-dn.net/?f=log_b%28b%29%20%3D%201)
Product rule:
![log_b(xy) = log_b(x) + log_b(y)](https://tex.z-dn.net/?f=log_b%28xy%29%20%3D%20log_b%28x%29%20%2B%20log_b%28y%29)
Division rule:
![\displaystyle log_b(\frac{x}{y}) = log_b(x) - log_b(y)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20log_b%28%5Cfrac%7Bx%7D%7By%7D%29%20%3D%20log_b%28x%29%20-%20log_b%28y%29)
Power rule:
![log_b(x^n) = n\cdot log_b(x)](https://tex.z-dn.net/?f=log_b%28x%5En%29%20%3D%20n%5Ccdot%20log_b%28x%29)
Change of base:
![\displaystyle log_b(x) = \frac{ log_a(x)}{log_a(b)}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20log_b%28x%29%20%3D%20%5Cfrac%7B%20log_a%28x%29%7D%7Blog_a%28b%29%7D)
Simplifying logarithms often requires the application of one or more of the above properties.
Simplify
![\displaystyle log_\frac{1}{2}(64)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20log_%5Cfrac%7B1%7D%7B2%7D%2864%29)
Factoring
.
![\displaystyle log_\frac{1}{2}(64)=\displaystyle log_\frac{1}{2}(2^6)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20log_%5Cfrac%7B1%7D%7B2%7D%2864%29%3D%5Cdisplaystyle%20log_%5Cfrac%7B1%7D%7B2%7D%282%5E6%29)
Applying the power rule:
![\displaystyle log_\frac{1}{2}(64)=6\cdot log_\frac{1}{2}(2)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20log_%5Cfrac%7B1%7D%7B2%7D%2864%29%3D6%5Ccdot%20log_%5Cfrac%7B1%7D%7B2%7D%282%29)
Since
![\displaystyle 2=(1/2)^{-1}](https://tex.z-dn.net/?f=%5Cdisplaystyle%202%3D%281%2F2%29%5E%7B-1%7D)
![\displaystyle log_\frac{1}{2}(64)=6\cdot log_\frac{1}{2}((1/2)^{-1})](https://tex.z-dn.net/?f=%5Cdisplaystyle%20log_%5Cfrac%7B1%7D%7B2%7D%2864%29%3D6%5Ccdot%20log_%5Cfrac%7B1%7D%7B2%7D%28%281%2F2%29%5E%7B-1%7D%29)
Applying the power rule:
![\displaystyle log_\frac{1}{2}(64)=-6\cdot log_\frac{1}{2}(\frac{1}{2})](https://tex.z-dn.net/?f=%5Cdisplaystyle%20log_%5Cfrac%7B1%7D%7B2%7D%2864%29%3D-6%5Ccdot%20log_%5Cfrac%7B1%7D%7B2%7D%28%5Cfrac%7B1%7D%7B2%7D%29)
Applying the logarithm of the base:
![\mathbf{\displaystyle log_\frac{1}{2}(64)=-6}](https://tex.z-dn.net/?f=%5Cmathbf%7B%5Cdisplaystyle%20log_%5Cfrac%7B1%7D%7B2%7D%2864%29%3D-6%7D)
Answer:
i think it a or b but i might be wrong
Step-by-step explanation:
sry if it is wrong tho